2011
DOI: 10.3945/jn.110.135806
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acid Load Is Not Associated with Lower Bone Mineral Density Except in Older Men,

Abstract: High dietary acid load may be detrimental to bone mineral density (BMD), although sufficient calcium intake might neutralize this effect. In observational studies, the association between BMD and dietary acid load, estimated by net endogenous acid production (NEAP) and potential renal acid load (PRAL), has been inconsistent, and the potential modifying effect of calcium intake has not been assessed. We therefore examined the cross-sectional associations of estimated NEAP and PRAL with BMD in the Framingham Ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
2
41
1
Order By: Relevance
“…Several studies suggest that these adverse effects may be mitigated by a reduction in the dietary acid load, although this area remains controversial (98, 99). In interventional studies, markers of bone resorption are reduced by potassium bicarbonate supplementation or consumption of the DASH diet (9, 100, 101).…”
Section: Relationship Of Acidosis and Dietary Acid Load To Morbidity mentioning
confidence: 99%
“…Several studies suggest that these adverse effects may be mitigated by a reduction in the dietary acid load, although this area remains controversial (98, 99). In interventional studies, markers of bone resorption are reduced by potassium bicarbonate supplementation or consumption of the DASH diet (9, 100, 101).…”
Section: Relationship Of Acidosis and Dietary Acid Load To Morbidity mentioning
confidence: 99%
“…One RCT showed pharmacologic doses of potassium citrate (alkaline substance) to be beneficial bone health [53]; however, two other RCTs showed no effect on BMD [54, 55]. Among men in the Framingham Original Cohort, dietary acid load estimated by NEAP was inversely related with femoral neck BMD, but no association was observed at the spine; no significant associations were observed in women [56]. No associations between NEAP and BMD were observed among men or women from the younger, Framingham Offspring cohort.…”
Section: Fruit and Vegetable Intakementioning
confidence: 99%
“…Similarly, other epidemiologic studies do not support the hypothesis that greater dietary acid load (associated with chronic high protein intake) is detrimental to bone health [8,18]. One study found that in men alone, greater dietary acid load may be detrimental to bone only under conditions of very low calcium intake [9▪].…”
Section: Epidemiologic Studiesmentioning
confidence: 99%